2017
DOI: 10.1016/j.cej.2017.03.120
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing sludge biodegradability through free nitrous acid pre-treatment at low exposure time

Abstract: The effectiveness of low free nitrous acid (FNA) pre-treatment times (PTs) (<8 h) on waste activated sludge (WAS) is not known. This study explores the effectiveness of four different FNA concentrations (0, 2.49, 3.55 and 4.62

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 28 publications
6
13
0
Order By: Relevance
“…Thus, the pretreatments disrupted cell walls and EPS in waste activated sludge due to their biocidal effect, which affects protein much more than polysaccharide. This agrees with previous studies, in which a similar trend is observed [12,33]. All three input variables, with p-value<0.05, had a significant effect on the model, while the effect of the input parameters on each other will be ignored due to p-value > 0.05.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the pretreatments disrupted cell walls and EPS in waste activated sludge due to their biocidal effect, which affects protein much more than polysaccharide. This agrees with previous studies, in which a similar trend is observed [12,33]. All three input variables, with p-value<0.05, had a significant effect on the model, while the effect of the input parameters on each other will be ignored due to p-value > 0.05.…”
Section: Discussionsupporting
confidence: 92%
“…The higher efficiency of combined pre-treatments in SCOD enhancement is attributable to the synergistic effect of radicals and oxidative chemicals released by FNA and Fenton reagent simultaneously. The SCOD enhancement from FNA pre-treatment, in this study, is in agreement with, but slightly higher than the research carried out by Zahedi et al [17] and Wang et al [26], which could be attributed to sludge specifications employed in this study.…”
Section: Degradation Of Organic Matterssupporting
confidence: 92%
“…It generates hydrogen peroxide (H2), peroxynitrite (ONOO-), nitrogen dioxide (˙NO2), hydroxide ion (˙OH -) and nitric oxide (˙NO) which have inhibitory impacts on key microorganisms in wastewater treatment plants at part per billion (ppb) levels [16]. Zahedi et al [17] demonstrated that after 5 hours of exposure time at 2.49 mg N-HN2/L, cells' viability in waste activated sludge declined by 80%, and methane production increased by 20%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions have been demonstrated to significantly enhance methane production (Zahedi et al, 2017a(Zahedi et al, , 2017b(Zahedi et al, , 2016). …”
Section: Fna Pre-treatment and Bmp Testsmentioning
confidence: 99%